Growth patterns, condition factors, and gonad maturity of the white-spotted spinefoot (Siganus canaliculatus, Park 1797) in the coastal area of Bontang City, East Kalimantan - Jusmaldi, Jusmaldi; Wahidah, Nurul; Hariani, Nova (Universitas Malikussaleh, 2023)
This study aims to analyze growth patterns, condition factors, and gonad maturity of the white-spotted spinefoot (Siganus canaliculatus, Park 1797) in coastal waters of Bontang City, East Kalimantan. Fish samples were collected every month from February to June 2020. Fish were collected using a simple random method from the catches of fishers who landed their fish at the Tanjung Limau port, Bontang City. Fish body length was measured using a digital caliper, and body weight was measured using a digital balance. The results of this study obtained a total of 226 individual fish, consisting of 110 males and 116 females. Male fish have a length ranged from 94.78-197.88 mm and a weight ranged from 18.24-94.30 g, while female fish have a body length ranged from 90.00-201.09 mm and a body weight ranged from 17.98-95.16 g. The length-weight relationship shows a strong correlation (r2=0.967) with the regression equation W=5x10-5L2.721. The fish growth pattern is negative allometric. The average condition factor was 1.08±0.09, which reflected good growth. Gonadal mature of fish are found in May and June, indicating that the fish are ready to spawn.Keywords: condition factor; growth; Siganus canaliculatus